WACANA EKOFEMINISME TIRTO.ID: TELAAH SIKAP MEDIA DALAM KONFLIK KARTINI KENDENG DENGAN PT. SEMEN INDONESIA - Fariz, Luxy Nabela; Andhita, Pundra Rengga (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2020)
This research aims to study how tirto.id's attitude towards ecofeminism discourse in Kartini Kendeng conflict with PT. Semen Indonesia in Rembang, Central Java, Indonesia. This study uses a qualitative descriptive method using Teun A. Van Dijk Critical Discourse Analysis (AWK) model which focuses on the elements of text, social cognition and social analysis. There are three data collection techniques that are carried out, namely, interviews, observation and literacy studies. The results showed that tirto.id had a fairly good consistency in raising the ecofeminism issue. Judging from the text elements, tirto.id presents themes, titles, leads, story telling and graphics that support the ecofeminism issue appearing in the community as a joint study that needs to be examined. Related to social cognition elements, tirto.id tried to build critical awareness about ecofeminism issue in Kartini Kendeng conflict with PT. Semen Indonesia. Until today the conflict is not over, Kartini Kendeng has consistently rejecting PT. Semen Indonesia, because it is cited, will have a destructive effect that has implications for the surrounding society. That capture is how tirto.id wants to build message through their writings. While from the social context elements, tirto.id has a holistic consideration compiling to raise the ecofeminism issue through the reporting of Kartini Kendeng. This report provides an opportunity for studies to open up the relationship between humans and the potential of environmental damage. tirto.id's consideration of preaching a special portion of the issue was able to take on the role of a bridge between reality inside and outside the text, giving rise to an inclusive perspective on women and the environment.